THE JURIDICAL ANALYSIS OF DEFAULT ON THE JOINT ACCOUNT SERVICE IN E-COMMERCE TRANSACTIONS - Susanto, Heri (Universitas Muhammadiyah Ponorogo, 2020)
The research described and analyzed the problems; (1) whether the online transactions through joint account have been suitable with the law in Indonesia; and (2) how the lawprotection of buyer and seller on the online transactions was if Balckpanda jointaccount performed the breach of contract. The research was descriptive-empirical law. The secondary data consisted of primaryand secondary law materials. The collecting data techniques were by interviewing theusers of Blackpanda joint account and by having literature study. Then, the data wereanalyzed in descriptive method. The research results were (1) The online transactions through joint account has fulfilledthe requirements for legally valid contract like acceptance, competency, considerationand legal intent; although based on the law no. 11 of 2008 on Electronic Informationand Transactions, Blackpanda joint account was failed to be safety and reliability ofprogrammable electronic system because it has performed the default like do notforward the money to the seller; (2) The law protection on the online transactionsthrough Blackpanda joint account based on the law no. 8 year 1999 concerningConsumer Protection could not protect the joint account consumers on the transactionsside and juridical guarantee on the use of joint account